Gnathostoma turgidum – still a mysterious parasite - Nawa Y.; Delgado-Vargas F.; Díaz-Camacho S. P. (Helminthologia)
The recent publication entitled “Possible zoonotic implications of the discovery of the advanced third stage larva of Gnathostoma turgidum (Spirurida: Gnathostomatidae) in a Mexican fish species” by Mosqueda-Cabrera et al., appeared in Helminthologia, 2023; 60(1): 112–116. was extremely interesting and informative showing potential zoonotic natue of G. turgidum. However, discovery of only one larva from one out of 17 fish rather indicate that this fish is an accidental host of G. turgidum. Whether this and other fish act as the second intermediate host in the life cycle of G. turgidum requires more field survey using both compression and digestion methods. Also, many biological events of G. turgidum such as intrahepatic maturation in the final hosts and the seasonal changes with self cure are remained unsolved. More extensive survey on intermediate and paratenic hosts for G. turgidum and biological research on unique features of G. turgidum is necessary.